Intertextuality in Educational Reform: Reflections on Equity in Swedish School Reform La Intertextualidad en las reformas educativas: reflexiones sobre la equidad en la reforma escolar sueca. - Guadalupe Francia (Arizona State University, 2008)
This article proposes intertextuality as a conceptual instrument for the deeper understanding of the phenomenon of equity in educational Reform in times of decentralization. This analysis starts from a dynamic vision of education reforms as interactions of texts. To illustrate the use of intertextual analysis of equity in education, this article introduces and discusses the analyzed examples of the educational national policy and of educational practice in the educational reform implemented in the 90?s and currently in force in the compulsory school in Sweden. It is argued that the meaning of equity is never a fixed one; it varies according to the interactions between political texts at a national level and texts of educational practice at communal and school levels. En este artículo se propone la intertextualidad como herramienta conceptual para lograr una mayor comprensión de la equidad en las reformas educativas en tiempos de descentralización. En este análisis se parte de una visión de reforma educativa como sistema dinámico de interacciones de textos. Para ilustrar la utilidad del análisis intertextual de la equidad educativa se presentan y discuten ejemplos de la política y de la práctica escolar en la reforma introducida en la década de los noventa y actualmente vigente en la escuela obligatoria sueca. Se argumenta que el significado de equidad nunca es fijo, sino que varía de acuerdo con las interacciones de los diferentes textos de la política educativa y de la práctica escolar.